Enhanced Microvasculature Formation and Patterning in iPSC–Derived Kidney Organoids Cultured in Physiological Hypoxia - Schumacher, Anika; Roumans, Nadia; Rademakers, Timo; Joris, Virginie; Eischen-Loges, Maria José; van Griensven, Martijn; LaPointe, Vanessa L.S. (Frontiers in Bioengineering and Biotechnology, 2022)
Graphical Abstract